Mechanical, hydrological and microstructural assessment of the durability of cemented paste backfill containing alkali-activated slag. Issue 2 (17th February 2018) - Cihangir, Ferdi; Akyol, Yunus
Abstract: The durability of full (FT) and deslimed sulphide-rich tailings (DT) cemented paste backfill (CPB) of alkali-activated slag (AAS; LSS–S: activated slag with aqueous sodium silicate and SH–S: activated slag with sodium hydroxide) was investigated based on the mechanical (strength), hydraulic and microstructural properties. DT and AAS improved the strength gain rate by decreasing the total- and macro porosity. DT and LSS–S configuration had a profound effect on strength development and produced 4.3–9.9-fold strengths than ordinary Portland cement (OPC) samples. DT also favoured the degree of cementation with dense packing matrix, decreased the permeability and thus, limited the adverse effects of acid and sulphate. DT hindered the decalcification of C–S–H leading to higher Ca/Si ratios for OPC while AAS samples exhibited approximately similar ratios over the curing period. SH–S led to drying shrinkage due to the greater amount of threshold pores. LSS–S/ DT combination provided better durability performance in case of aggressive environments by improving the microstructure of CPB.